Analisis Faktor-Faktor yang Mempengaruhi Tingkat Kelahiran di Kabupaten Brebes dengan Pendekatan Regresi Logistik Biner - Roni Guntara; Safa’at Yulianto (Universitas Muhammadiyah Semarang, 2017)
The birth rate is affected by the age of first marriage, family planning program, education level, employment status and length of marriage. To determine therelationship and influence of first marriage age, the participation of familyplanning program, education level, employment status and length of marriageto birth rate according to number of children born used binary logisticregression method.Chi-Square test shows that the variable length of marriage issignificant to birth rate. While the age of first marriage, the participation offamily planning programs, the level of education and employment status is notsignificant. Based on binary logistic regression analysis obtained model that is:logit function model:Keywords: Chi-Square, Binary Logistic Regression, Birth Rate